Response of Cocoa Seed Growth Received by Bio-priming Technique Treatment - Maretik Maretik (Journal of Biological Science and Education, 2021)
Cocoa (Theobroma cacao L.) is one of the people's plantation crops with promising prospects because it can flower and bear fruit throughout the year. One of the efforts to improve the quality of cocoa seeds is by increasing the viability and vigor of seeds through seed invigoration techniques. This study aimed to determine the effect of biopriming invigoration treatment techniques in increasing cocoa seeds' viability, vigor, and growth. This research was conducted at the Laboratory of Agronomy Unit of the Faculty of Agriculture of Halu Oleo Kendari from April to May 2019. This study used a completely randomized design (CRD) consisting of 4 treatments: Control (B0), Bio-priming Bacillus sp. CKD061 (B1), Bio-priming Pseudomonas flourescent (B2), a combination of Bio-priming Bacillus sp. CKD061 with Pseudomonas fluorescent. Each treatment was repeated three times, so there were 12 experimental units. The data obtained were analyzed using variance analysis and continued using the Least Significant Difference Test (LSD). Based on the results of research that biopriming treatment using rhizobacteria has the best influence on the viability, vigor and growth of cocoa seeds. Keywords: Biopriming, cocoa seeds, rhizobacteria, seed growth